Sistem Informasi Monitoring Dan Evaluasi Vaksinasi Wilayah Provinsi Lampung - Hendra Kurniawan; Denny Andreas; Neni Purwati; Sri Karnila; Nurjoko; Egi Safitri; Ruki Rizal (TEKNIKA, 2023)
Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been previously identified in humans. Residents in the Lampung Province Region, especially the East Lampung Regency area. The community has difficulty seeing the vaccination distribution map, they still use table data containing only the names and types of vaccines made by the East Lampung Health Service. The data collection is computerized but the data is presented in tabular form, using Google Forms, converted using Google Sheets and then reported to the district to be submitted to the East Lampung Health Office. Meanwhile, system development uses the Agile Development method. This research produces a web-based geographic information system that can display data in the form of a map of the distribution of covid-19 vaccination locations for the Lampung Province, especially East Lampung Regency. Keywords: Coronavirus Disease, Vaccination, Geographic Information System